AFRICAN MULTILATERAL RESPONSES TO THE CRISIS IN ZIMBABWE: A RESPONSIBILITY TO PROTECT PERSPECTIVE (The Strategic Review for Southern Africa, 2020)
The Responsibility to Protect (RtoP) represents one of the key normative developments towards mitigating global human rights violations. Normatively, the RtoP advances the notion of responsible sovereignty by obligating states to protect their people from humanitarian catastrophe and emphasises the residual role of the international community in the event of lack of capacity or the state's unwillingness to protect. It is in this context that this article examines RtoP mitigation measures instituted by the South African Development Community (SADC) and the African Union (AU) as regional multilateral institutions in responding to the crisis in Zimbabwe. The article considers the extent to which the responses have been guided implicitly or explicitly by RtoP principles. The evolution and consolidation of the humanitarian crisis has been considered, with specific focus on the human security impact of government policies, in particular, Operation Murambatsvina (the destruction of what were deemed illegal housing structures in major cities in Zimbabwe in May 2005) and the unprecedented 2008 electoral violence as a result of increased militarisation of governance structures. Debate on the applicability of RtoP to the crisis in Zimbabwe is thus located within the broader framework of the normative theories of international relations that forms the basis of RtoP. The article argues that escalation of the government induced humanitarian crisis was as a result of lack of timeous or effective responses by both the AU and SADC. Again, the AU and SADC responses were significantly influenced by diverse, often mutually exclusive, interpretations of the main causes of the crisis. Another salient finding is the extent to which politicisation of RtoP and lack of political will undermined RtoP operationalisation.
Keywords: Responsibility to Protect; RtoP; Global Human Rights; responsible sovereignty; humanitarian catastrophe; Southern African Development Community; SADC; African Union; AU; Zimbabwe; Operation Murambatsvina; Strategic Review for Southern Africa; vol 39 no 2 November 2017